1993
DOI: 10.1016/0379-6779(93)91180-a
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR absorption spectroscopy of BEDT-TTF radical salts: charge transfer and donor-anion interaction

Abstract: IR absorption spectra from various K-phases of BEDT·TfF radical cation salts as well as from a-(BEDT·TIFhI, arc presented. From tbese spectra one special mode l'n representing the asymmetric ring C-C stretching vibration is assigned and the dependence of its frequency from the average charge on the donor molecule is given. The investigation of the metal-insulator phase transition of a-(BEDT·TrF)2I, at 135 K with respect to this vibrational model lin gives strong indication of a charge localization in at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 23 publications
(15 reference statements)
6
48
0
Order By: Relevance
“…The Fermi surface consists of small pockets on the Brillouin zone boundary, which are two-dimensional in nature, but created from a onedimensional Fermi surface crossing the Brillouin boundary. In agreement with this, recent MIR absorption Illeasurements [33,34] indicate a localization of charge in one of the two different stacks of the donor molecules. This would imply that the crystals lose their .quasi two-dimensional electronic properties below the phase transition and exhibit more quasI onedimensional properties, since the coupling between neighboring stacks is reduced or lost.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The Fermi surface consists of small pockets on the Brillouin zone boundary, which are two-dimensional in nature, but created from a onedimensional Fermi surface crossing the Brillouin boundary. In agreement with this, recent MIR absorption Illeasurements [33,34] indicate a localization of charge in one of the two different stacks of the donor molecules. This would imply that the crystals lose their .quasi two-dimensional electronic properties below the phase transition and exhibit more quasI onedimensional properties, since the coupling between neighboring stacks is reduced or lost.…”
Section: Introductionsupporting
confidence: 65%
“…They are responsible for a change in the charge distribution within the molecule, the dimerization, and the interaction between neighboring BEDT-TTF molecules. The result of the IR reflectivity and absorption [33,34] point in this direction, as do thermal expansion measurements [29].…”
Section: Discussionmentioning
confidence: 99%
“…Later, Chow reported a similar charge order for (TMTTF) 2 X (X = PF 6 , AsF 6 ) using 13 C-NMR [11]. In the case of a two-dimensional organic compound, Moldenhauer et al, reported that localization of charge occurs in one of the stacks of α-(BEDT-TTF) 2 I 3 (BEDT-TTF corresponds to bis(ethylenedithio) tetrathiafulvalene) [12]. After the theoretical prediction of the CO ground state for α-(BEDT-TTF) 2 I 3 by Kino and Fukuyama [13], CO in two-dimensional organic compounds was suggested in α-(BEDT-TTF) 2 I 3 [14], and more clearly shown in θ-(BEDT-TTF) 2 RbZn(SCN) 4 [15].…”
Section: Introductionmentioning
confidence: 89%
“…Kino and Fukuyama examined the effect of on-site Coulomb interaction within the Hartree-Fock approximation, and they predicted that a charge localization with a vertical stripe is the cause of the MI transition [13,126]. Before the theoretical prediction, Moldenhauer et al, reported that the localization of electrons occurs at the B and C sites whereas the electrons at the A and A′ sites are delocalized below T MI [12]. The 13 C-NMR study suggested the existence of two differently charged molecules below T MI [119,127].…”
Section: α-(Bedt-ttf) 2 I 3 and Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation